Accuracy of Intraoperative Mechanical Axis Alignment to Long-Leg Radiographs following Robotic-Arm–Assisted Unicompartmental Knee Arthroplasty - Roche, Martin W.; Vakharia, Rushabh M.; Law, Tsun Y.; Sabeh, Karim G. (The Journal of Knee Surgery, 2022)
Improper alignment and implant positioning following unicompartmental knee arthroplasty (UKA) has been shown to lead to postoperative pain and increase the incidence of revision procedures. The use of robotic-arm assistance for UKA (RAUKA) has become an area of interest to help overcome these challenges. The accuracy of intraoperative alignment compared with standing long-leg X-rays postoperatively following medial RAUKA has been in question. Therefore, the purpose of this study was to (1) determine final mean intraoperative coronal alignment in extension utilizing an image based intraoperative navigation system, and (2) compare final intraoperative alignment to 6-week weight-bearing (WB) long-leg X-rays. Patients who underwent RAUKA for medial compartmental osteoarthritis were identified from January 1, 2018, to August 31, 2019, through our institution's joint registry. The query yielded 136 (72 right and 64 left) patients with a mean age of 72.02 years and mean body mass index (BMI) of 28.65 kg/m2 who underwent RAUKA. Final intraoperative alignment was compared with WB long leg X-rays 6 weeks postoperatively by measuring the mechanical alignment. Statistical analysis was primarily descriptive. Pearson's correlation coefficient was used to determine the relationship between intraoperative alignment to 6-week alignment. A p-value of <0.05 was considered statistically significant. Mean intraoperative coronal alignment after resections and trialing was 4.39 varus ± 2.40 degrees for the right knee, and 4.81 varus ± 2.29 degrees for the left knee. WB long-leg X-rays 6 weeks postoperatively demonstrated mechanical axis alignment for the right and left knees to be 3.01 varus ± 2.10 and 3.7 varus ± 2.38 degrees, respectively. This resulted in a change in alignment of 1.36 ± 1.76 and 1.12 ± 1.84 degrees for the right and left knees, respectively (p < 0.05). Pearson's correlation coefficient demonstrated a correlation of 0.69 between intraoperative to long-leg-X-ray alignment. RAUKA demonstrates excellent consistency when comparing postoperative WB long-leg X-rays to final intraoperative image-based non-WB alignment.
Keywords: Robotic assisted; unicompartmental knee arthroplasty; mechanical alignment; accuracy